Comparison of Ultrasonography with Cole’s Formula to Determine Appropriate Endotracheal Tube Size in Pediatric Population - Shaheed, Asadh M; Shrestha, Bibhush; Pradhan, Bishwas; Shrestha, Anil; Parajuli, Bashu D (Journal of Institute of Medicine Nepal, 2022)
Introduction Recently, ultrasonography (USG) has gained popularity in perioperative airway management . One of the commonest method to select endotracheal tube in pediatric patients is Cole’s formula. Our study was conducted to assess if there was a measurable difference in the appropriateness of the endotracheal tubes as selected by the two methods. Methods The study group included 68 ASA physical status I and II children (aged 2-6) years scheduled for elective surgeries under general anesthesia with endotracheal intubation in an randomized prospective manner. The size of endotracheal tube was calculated using Cole’s formula in group A. In group B, ultrasound was done to measure the subglottic transverse diameter at the level of cricoid to find the largest outer diameter of tube . Results Ultrasonography group measuring the subglottic diameter was found to have more appropriately sized tubes than age-based Cole's formula (76.5% Vs 58.8% p=0.007). The pressure equilibrated measured (13.2 ± 5.2 cm of H2O in age based group and 17 ± 4.5 cm of H2O in ultrasonography group) was statistically significant (p= 0.002). Also the incidence of selecting an inappropriately small sized ET tube was lower in the ultrasound group (5.9% Vs 35.3%).There were no significant differences in the number of intubation attempts and mean time required for intubation between the two groups. Conclusion Ultrasonographic method is a suitable alternative tool in predicting the size of uncuffed endotracheal tube in pediatric population than age-based Cole’s formula.